Addressing logistics land in spatial planning. An exemplary evaluation of state and regional plans - Thiemermann, Andre (Raumforschung und Raumordnung | Spatial Research and Planning, 2025)
Currently, there are reasons for taking logistics up in spatial planning, including the large land consumption of logistics facilities and the urgent implementation of a sustainable transport system. One planning option is to secure suitable land for logistics facilities in formal spatial development plans. To date, only a limited number of studies have been carried out on this specific implementation. This paper uses 17 regional plans as examples to examine the planning instruments and planning focus with which this task is currently being implemented in German regional plans. The analysis of the regional plans at hand shows that half of the regional plans use planning instruments to address logistics facilities. In some regional plans, only defined logistics segments are addressed in planning, e.g. the establishment of port-related industries in the proximity of ports. To term land for logistics infrastructure like ports and inland terminals on the other hand, is much more established and is included in almost all plans. Taking up planning for locations of logistics facilities in regional plans takes place when logistics is defined as an economic focus, logistics is considered relevant for the functioning of the regional economy or planning locations for logistics facilities are required by state planning regulations.